(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
HIV/AIDS continues to pose a serious public health threat, especially among adolescents who face heightened vulnerability due to limited knowledge, pervasive stigma, and inadequate sexual health education. In Indonesia, individuals aged 15–24 represent a substantial portion of new HIV infections. Factors such as misinformation, cultural taboos, and lack of open discussion contribute to low awareness and riskier behaviors in this age group. To address these challenges, an educational intervention was conducted involving secondary school students. The session featured an engaging video, a presentation by a health educator, and post-intervention questionnaire to assess changes in students’ knowledge and attitudes toward HIV/AIDS. The approach aimed to encourage dialogue, correct misconceptions, and reduce stigma through interactive learning. The intervention proved effective in fostering awareness and openness. After the session, 83% of students acknowledged the importance of HIV/AIDS education, and 63% indicated a willingness to undergo testing—reflecting reduced stigma. Additionally, 87% expressed interest in participating in future sessions. However, only 33% cited schools as their primary source of information, while 47% relied on social media, and just 20% received information from family or peers. These findings highlight the need to strengthen school-based programs and improve media literacy. Empowering adolescents as peer educators can promote sustained behavioral change and help build a more informed and empathetic generation.